Co-Creation of High-Tech Products in the B2B Domain - Grafmüller, Leontin (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
Leontin Karl Grafmüller explores how companies can better manage co-creation in the B2B high-tech domain. Co-creation is an active, creative and social collaboration process between customers and providers, in which customers become active participants in innovation processes of a firm to jointly develop new products. The co-creation of high-tech products poses several challenges related to high product complexity such as the time intensity or incorrect specifications. The author investigates this topic from different angles and showcases how the challenges involved are faced to enhance both the efficiency and efficacy of the co-creation of high-tech products in the B2B domain.<br